Nickel-catalyzed C(2)-H arylation of indoles with aryl chlorides under neat conditions - Pandey, Dilip K.; Vijaykumar, Muniyappa; Punji, Benudhar (Journal of Organic Chemistry, 2019)
Nickel-catalyzed regioselective C(2)-H arylation of indoles and pyrroles with aryl chlorides is achieved under neat conditions. This method allows the efficient coupling of diverse aryl chlorides employing a user-friendly and inexpensive Ni(OAc)(2)/dppf catalyst system at 80 degrees C. Numerous functionalities, such as halides, alkyl ether, fluoro-alkyl ether, and thioether, and substituted amines, including heteroarenes like benzothiazolyl, pyrrolyl, indolyl, and carbazolyl, are well tolerated under the reaction conditions. The preliminary mechanistic study highlights a single-electron transfer (SET) pathway for the arylation reaction.